Simulation and database society in Japanese role-playing game fandoms: Reading boys' love dōjinshi online - Lucy Hannah Glasspool (Transformative Works and Cultures, 2013)
Japanese video games have been characterized as typifying contemporary postmodernity in the form of simulacra, both as a media form and in terms of their extensive localization for international markets, which creates user fantasies of Japaneseness that are not linked to an authentic or original Japan. These simulations are reappropriated by fans to create new content, in this case boys' love dōjinshi, which are in turn disseminated and consumed in an English-speaking online context. Fantasy role-playing video games, which often privilege heteronormativity and binary gender norms in their goals, narratives, and aesthetics, are among the most popular texts reimagined in this way. This study considers the concepts of simulation and database societies through an examination of the ways in which artificial contours of Japaneseness are constructed in the role-playing game series Final Fantasy VII's boys' love dōjinshi fandoms, how far these fan texts develop possibilities for the deconstruction of heteronormativity, and how transnational digitized consumption methods facilitate the intersection of these phenomena.